(untitled) (Abhat Journal, 2024)
Epidemics in general, and the plague in particular, were among the most dangerous things that human societies were exposed to in the era of medieval history, and before the plague was a deadly disease that suddenly appeared and spread rapidly. It was an important historical event that disturbed peoples throughout their history, and remained present in the memory of nations and civilizations. On absolute terror and eternal terror; Because of its profound effects on both levels: Material and spiritual for the societies that experienced it, and its occurrence and epidemic spread were always accompanied by the destruction of the human power of these societies, and the paralysis of their population and economic growth, and due to the many dangers it caused, and the major transformations it led to, from which the European West suffered over the course of the second half of the eighth century and the following century ; Countries have been keen, and are still keen, to adopt measures to prevent its occurrence and limit its progression and spread.